Adult movements and population dynamics of two bamboo aphids (Hemiptera: Aphididae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The paper deals with the development, parametrization and validation of models that represent the dynamics of age-structured Takecallis arundinariae (Essig) and T. taiwanus (Takahashi) populations on bamboo. These models are based on the matrices of Leslie (1945) and Letkowitch (1965) and explain the observed infestation patterns on the basis of temperature effects on development, fecundity and survival. A key role is given to the movements of adults between the bamboo plot under study and the surroundings. Previously published observations and experiments carried out in the nursery are used for both parameter estimation and validation of the model, which satisfactorily represents the observed infestation patterns, indicates limitations (the developmental rate is linearly related to the temperature) and shows the possibilities for extending the study to the whole year.
Keywords: Takecallis arundinariae; Takecallis taiwanus; bamboo; matrix model; temperature effects; movement